2020
DOI: 10.3390/cancers12092577
|View full text |Cite
|
Sign up to set email alerts
|

A Modern Approach to Endometrial Carcinoma: Will Molecular Classification Improve Precision Medicine in the Future?

Abstract: Endometrial cancer has been histologically classified as either an estrogen-dependent cancer with a favorable outcome or an estrogen-independent cancer with a worse prognosis. These parameters, along with the clinical attributions, have been the basis for risk stratification. Recent molecular and histopathological findings have suggested a more complex approach to risk stratification. Findings from the Cancer Genome Atlas Research Network established four distinctive genomic groups: ultramutated, hypermutated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…Thus, identification of reliable testing strategies is crucial for the best patient treatment options. Currently, IHC is widely recommended as a robust initial testing tool for the detection of dMMR in EC [ 30 ]. However, IHC still has its limitation due to inconclusive staining results in some of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identification of reliable testing strategies is crucial for the best patient treatment options. Currently, IHC is widely recommended as a robust initial testing tool for the detection of dMMR in EC [ 30 ]. However, IHC still has its limitation due to inconclusive staining results in some of the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective studies revealed a potential impact of the molecular-based classification of EC on EC patients in the clinics. ESGO and ESTRO have recommended a new molecular-based clinicopathological risk stratification system for adjuvant treatment [81], where POLE-mt was assigned to the low-risk and MSI, CNH, and CNL were assigned to the intermediate-to high-risk group. In the high-risk group, chemoradiation and EBRT were recommended.…”
Section: Potential Clinico-molecular Guided Risk Stratification and Treatment Benefit In Hr-ecsmentioning
confidence: 99%
“…Endometrial cancer (EC) is the most prevalent cancer of the female reproductive tract in countries ranked within the highest tier of the human developmental index, with obesity being a strong predisposing factor 1 , 2 . While most EC patients have a favorable prognosis, identification of high-risk EC disease is essential to determine optimal surgical treatment and potential adjuvant therapies 3 , 4 . Preoperative risk stratification is based on endocervical curettage (biopsy) or endometrial pipelle sample often combined with preoperative imaging, such as pelvic magnetic resonance imaging (MRI) for local staging 3 , 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%